Developing Printable Reading Test to Foster Reading Comprehension among Pesantren Students in Low-Technology Environments in Closed Tests - Abdullah Salim, Mochammad; Ayu Lestari, Annisa (ENJEL: English Journal of Education and Literature, 2025)
This study aims to develop and evaluate a printable reading comprehension test specifically designed for pesantren students in low-technology learning environments. Utilizing the ADDIE instructional design model—comprising Analysis, Design, Development, Implementation, and Evaluation—the research addresses the digital divide and material constraints often found in religious educational settings. The methodology employed a Research and Development (R&D) design involving ten students from MA Al Mahrusiyah at Daru Zainab, selected through purposive sampling. Data collection involved a printable closed-test format, specifically a fill-in-the-blank assessment, supplemented by semi-structured interviews to capture qualitative insights. Quantitative results indicated a significant improvement in reading proficiency, with mean scores rising from 5.40 in the pretest to 9.10 in the post-test. A paired-sample t-test confirmed this improvement was statistically significant (p < 0.05). Qualitative findings further revealed that the structured, context-sensitive nature of the test helped students focus on deeper meaning rather than guessing. While the study is limited by its small sample size and short-term scope, it demonstrates that systematic instructional design can bridge the gap between pedagogical theory and real-world educational constraints. Ultimately, this research provides a feasible and effective alternative for fostering reading comprehension in under-resourced environments where digital tools are impractical.